2020
DOI: 10.1371/journal.pone.0242913
|View full text |Cite
|
Sign up to set email alerts
|

Significant reductions of host abundance weakly impact infection intensity of Batrachochytrium dendrobatidis

Abstract: Infectious diseases are considered major threats to biodiversity, however strategies to mitigate their impacts in the natural world are scarce and largely unsuccessful. Chytridiomycosis is responsible for the decline of hundreds of amphibian species worldwide, but an effective disease management strategy that could be applied across natural habitats is still lacking. In general amphibian larvae can be easily captured, offering opportunities to ascertain the impact of altering the abundance of hosts, considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 62 publications
0
6
1
Order By: Relevance
“…Our results differ from previous field studies that did not find evidence of persistent effects of itraconazole treatment on apparent survival or Bd infection (Bosch et al 2015;Hudson et al 2016;Geiger et al 2017; Knapp et al 2022 [this study found persistent effects of treatment for adults, but not for earlier life stages]). Our treatment targeted a specific period (shortly after metamorphosis) when Cascades frogs are highly susceptible to Bd and experience dramatic increases in Bd prevalence (Hardy et al 2015).…”
Section: Effects Of Treatment On Early Postmetamorphic Life Stagescontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results differ from previous field studies that did not find evidence of persistent effects of itraconazole treatment on apparent survival or Bd infection (Bosch et al 2015;Hudson et al 2016;Geiger et al 2017; Knapp et al 2022 [this study found persistent effects of treatment for adults, but not for earlier life stages]). Our treatment targeted a specific period (shortly after metamorphosis) when Cascades frogs are highly susceptible to Bd and experience dramatic increases in Bd prevalence (Hardy et al 2015).…”
Section: Effects Of Treatment On Early Postmetamorphic Life Stagescontrasting
confidence: 99%
“…In addition, we hypothesize that metamorphs emerging from surface-water pools may be more susceptible to infection than those emerging from fens because temperatures in pools may regularly exceed the frog's thermal optimum (i.e., the thermal mismatch hypothesis for cool-adapted species; Cohen et al 2017;Sauer et al 2020), and because rapid dry down of pools may decrease post-metamorphic immune function (Gervasi & Foufopoulos 2008;Rollins-Smith et al 2011;Kohli et al 2019). However, it is also possible that larval habitats differed in other factors that could be related to Bd infection, including density and contact rates (Rachowicz & Briggs 2007;Briggs et al 2010;Bosch et al 2020) and host genetic factors related to Bd resistance (e.g., Savage & Zamudio 2011Bataille et al 2015). Such effects of larval habitat may play an important role in determining the impact of climatic change on interactions between amphibians and Bd.…”
Section: Effects Of Larval Habitat On Bd Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore predict that the magnitude of host population declines following Bd invasion should increase for higher host population density prior to decline (branch point 2–4). Finally, while it is often assumed that the accumulation of Bd infection intensity following initial infection is driven by within‐host processes and is largely decoupled from the density of hosts in the environment (DiRenzo et al, 2018; Wilber et al, 2017), there is some evidence that host density can influence chytrid infection intensity (Bosch et al, 2020; Tompros et al, 2022). We test this hypothesis and predict that host density in enzootic and epizootic scenarios will not have a clear effect on Bd infection intensity (branch point 2).…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, there has been a dramatic decline in some species that are highly susceptible to Batrachochytrium , such as the midwife toad ( Alytes obstetricans , Fig. 2 ) (Bosch et al 2020 ). Microbiological studies of heritage monuments, particularly those using metagenomic tools, should focus on detecting and highlighting the occurrence of emergent pathogens in cultural sites, to prevent making these frequently visited site sources of the spread of hazards either to humans or to other organisms.…”
Section: Overlooked Strains: Pathogens and Novel Antibioticsmentioning
confidence: 99%